Application of Ribonucleic Acid (RNA) in Forensic Sciences - Muhammad Jawad; Saadia Noreen; Muhammad Faheem Ashraf; Maryam Asif; Hafiza Misbah Asif; Saqib Ali; Allah Rakha (BioMedica, 2020)
Forensic science has been helping law enforcement agencies in better understanding and presenting the evidence in the court of law. In certain situations, when conventional forensic methods of investigations cannot make better conclusions with more specific accuracy, then molecular techniques do help in reaching the acquired accuracy in the results regarding the identification of evidence. Advanced molecular techniques, which are using Deoxyribose Nucleic acid (DNA), Ribose Nucleic Acid (RNA), and protein molecules to produce forensically important information from the samples recovered at the crime scene. DNA can only distinguish among individuals but is unable to discriminate the type of samples originated from the same sample. For this RNA has become a molecule of interest for its different levels of expressionin different cells/tissues of an individual. RNA molecules of different types are being used to build up models for several purposes (injury-age, new-born age, molecular cause of death, etc.). Modern techniques like Real-time Polymerase Chain Reaction (PCR) and Microarray are being used for the detection of RNA molecules of interest both in the form of its abundance and as a unique molecular detection. This script will help in understanding the importance of RNA application in forensic sciences by providing an overview of the research done to date and the techniques being used for this purpose.